The transformative power of AI: projected impacts on the global economy by 2030 - Banerjee, Anita; Kabadi, Smeeta; Karimov, Dostonbek (Review of Artificial Intelligence in Education, 2023)
Objective: The primary focus of this document is to delve into the role and influence of Artificial Intelligence (AI) on the global economy. The study aims to elucidate the potential economic ramifications, both positive and negative, that AI technologies might bring. Conclusions: Preliminary insights suggest that artificial intelligence has the potential to significantly boost the global economy. For instance, AI could potentially add up to 16%, approximately 13 trillion, to the global economy by 2030. Furthermore, AI’s influence could elevate the global GDP by up to 26%. It is also highlighted that in the upcoming years, at least 70% of companies worldwide will integrate AI in some form or another. Practical Implications: The rapid adoption of AI technologies will undeniably have profound implications on businesses and economies. Companies that leverage AI stand to gain competitive advantages in their respective domains. Additionally, as more businesses adopt AI, there will be a heightened demand for AI expertise, potentially leading to job creation in specific sectors while possibly leading to job redundancies in others.